Alternate current biosusceptometry for the assessment of gastric motility after proximal gastrectomy in rats: a feasibility study - Calabresi, M. F. F. [UNESP]; Quini, C. C. [UNESP]; Matos, J. F. [UNESP]; Moretto, G. M. [UNESP]; Americo, M. F.; Graça, J. R. V.; Santos, A. A.; Oliveira, R. B.; Pina, D. R. [UNESP]; Miranda, J. R. A. [UNESP] (Wiley-Blackwell, 2015)
This study proposes an experimental model to assess the consequences of gastric surgeries on gastric motility. We investigated the effects of proximal gastrectomy (PG) using a non-invasive technique (alternate current biosusceptometry [ACB]) on gastric contractility (GC), gastric emptying (GE), and orocecal transit (OCT) after the ingestion of liquids and solids in rats. Twenty-four male rats were subjected to gastric motility assessment before and after the PG procedure. The GE and OCT results are expressed as the mean time of gastric emptying (MGET) and cecum arrival (MCAT). The GC recordings are presented as the frequency and amplitude of contractions. Mean time of gastric emptying after solid meals were significantly different (p < 0.001) between control and PG (113 ± 5 to 99 ± 6 min). Mean time of cecum arrival ranged from 265 ± 9 to 223 ± 11 min (p < 0.001) and 164 ± 9 to 136 ± 17 min (p < 0.050) for solid and liquid meals, respectively. The assessment of GC showed that surgery decreased the phasic frequency (4.4 ± 0.4 to 3.0 ± 1.1 cpm, p < 0.050) and increased the amplitude of contractions (3.6 ± 2.7 to 7.2 ± 3.0 V/s, p < 0.050). No significant difference was found in tonic frequency. The ACB system was able to assess GE, OCT, and GC in gastrectomized rats. Overall, PG accelerated GE and gastrointestinal transit, likely due to the increase in both intragastric pressure and amplitude contraction. Our data presented an efficient model to investigate functional consequences from gastric surgeries that will allow further studies involving different procedures.
Keywords: Ac biosusceptometry; Gastric contractility; Gastric emptying; Gastric motility; Proximal gastrectomy